EFFECT OF GROWTH REGULATORS ON CLUSTERBEAN [CYAMOPSIS TETRAGONOLOBA (L.)] GROWTH UNDER ARAVALI HILLS ENVIRONMENT IN RAJASTHAN - V. K. MEENA; M. K. KAUSHIK; R. S. MEENA; V. S. MEENA; B. P. MEENA (The Bioscan, 2014)
A field experiment was conducted during the season kharif 2008 and 2009 to find out response of clusterbean to growth regulators. Twenty eight treatment combinations i.e. four varieties (RGC-936, RGC-1002, RGC-1003 and RGC-1017) as main plot treatment and seven growth substances (control, seed treatment with thiourea 500 ppm, foliar application of thiourea 500 ppm, seed + foliar application of thiourea 500 ppm, seed treatment with TGA 100 ppm, foliar application of TGA 100 ppm and seed + foliar application of TGA 100 ppm) as sub-plot treatment was laid out in split-plot design with three replications. The results of the experiment showed that variety RGC-936 gave significantly higher plant height at harvest, dry matter accumulation at 30 DAS, 45 DAS and 60 DAS and at harvest. The application of seed + foliar application of thiourea 500 ppm show significant improvement on growth parameters viz., plant height at harvest, days to maturity, dry matter accumulation at 30 DAS, 45 DAS, 60 DAS and at harvest than the other treatments.